Invasive Insects: Management Methods Explored. Issue 5 (14th October 2019) - McLaughlin, Gemma M; Dearden, Peter K
Abstract: Invasive insect species can act as a plague across the globe, capable of vast expansion and rapid, proliferate reproduction. The spread of pathogens of serious diseases such as malaria and Zika virus and damages to agricultural crops number some of the afflictions invasive insects provide to humans alone. Additionally, an escape from predators can fail to keep invasive insects in check, providing potential threats such as extra resource competition to native species when insects invade. A variety of methods are employed to combat these invasive species, each with their own varying levels of success. Here, we explore the more traditional methods of invasive insect pest control, such as pesticides and biological control. In lieu of several unintended consequences resulting from such practices, we suggest some should be abandoned. We evaluate the potential of new techniques, in particular, those with a genetic component, regarding the costs, benefits and possible consequences of implementing them. And finally, we consider which techniques should be the focus of future research, if we truly wish to manage or even eradicate invasive insects in their introduced lands.